Conserved Autophagy Pathway Contributes to Stress Tolerance and Virulence and Differentially Controls Autophagic Flux Upon Nutrient Starvation in Cryptococcus neoformans - Zhao, Xueru; Feng, Weijia; Zhu, Xiangyang; Li, Chenxi; Ma, Xiaoyu; Li, Xin; Zhu, Xudong; Wei, Dongsheng (Frontiers in Microbiology, 2019)
Cryptococcus neoformans is a major fungal pathogen primarily infecting immunocompromised hosts. Autophagy is mainly a catabolic process induced by and coping with nutrient deficiency and various stressful conditions. Human environment often imposes various stresses to C. neoformans and therefore, autophagic responsiveness of C. neoformans to these stresses often decides its survival in host. However, a systematic study on how these ATG genes influence these phenotypes in C. neoformans is still lacking. In this study, 22 ATG-deficient strains were constructed to investigate their roles in virulence, pathogenesis, stress response, starvation tolerance and autophagic flux in C.neoformans. We found several interesting points. 1 Atg6 and Atg14-03, have a significant impact on the ability of growth at 37℃ and laccase production. 2 Atg2∆ and atg6∆ strains were also sensitive to oxidative stress caused by H2O2. 3 About half of atg∆ strains displayed a higher sensitivity to 1.5 M NaCl and remarkable lower virulence than WT in Galleria mellonella model. 4 Autophagic flux was dependent on Atg1-Atg13 complex, Atg5-Atg12-Atg16 complex, Atg2-Atg18 complex and Atg11, GFP-Atg8 cleavage was hardly detected in these autophagy-defective mutants. 5 More interestingly, cleavage of GFP-Atg8 was still observed in atg3∆, atg4∆, atg6∆ and atg14∆ strains. 6 There is no obvious ATG10 homologs in this fungus. 7 These ATG genes contribute differentially to carbon and nitrogen starvation tolerance comparing with S. cerevisiae. This investigation provided very useful information about the specific roles played by ATG genes in Cryptococcus neoformans.